МОДЕЛИРОВАНИЕ ЭНЕРГОСБЕРЕГАЮЩЕГО АСИНХРОННОГО ДВИГАТЕЛЯ ДЛЯ ЭЛЕКТРОПРИВОДА МЕХАНИЗМОВ ПОСТУПАТЕЛЬНОГО ДВИЖЕНИЯ - Юнусов, Рустем; Имомназаров, Азизбек; Бобокулов, Завкиддин (Innovatsion texnologiyalar, 2022)
In the technological processes of the production of the agro-industrial complex, mechanisms with the translational movement of the working bodies are used. For such mechanisms, electric drives with linear asynchronous motors are very effective. A numerical method based on detailed equivalent circuits for electric and magnetic circuits of an asynchronous electric motor allows you to take into account all their features to the fullest extent. On mathematical and physical models, the traction and energy performance of linear asynchronous electric motors with different schemes for connecting the inductor windings, designs of the secondary element and modes have been studied.